Brand-specific influenza vaccine effectiveness estimates during 2019/20 season in Europe – Results from the DRIVE EU study platform. Issue 29 (29th June 2021) - Stuurman, Anke L.; Biccler, Jorne; Carmona, Antonio; Descamps, Alexandre; Díez-Domingo, Javier; Muñoz Quiles, Cintia; Nohynek, Hanna; Rizzo, Caterina; Riera-Montes, Margarita; ,
Highlights: Brand-specific influenza vaccine effectiveness was estimate for the 2019/20 season. The DRIVE network consisted of 13 sites from 7 European countries. Abstract: DRIVE (Development of Robust and Innovative Vaccine Effectiveness) is an IMI funded public–private platform that aims to annually estimate brand-specific influenza vaccine effectiveness (IVE), for public health and regulatory purposes. IVE analyses and reporting are conducted by public partners in the consortium. In 2019/20, four primary care-based test-negative design (TND) studies (Austria, England, Italy (n = 2)), eight hospital-based TND studies (Finland, France, Italy, Romania, Spain (n = 4)), and one population-based cohort study (Finland) were conducted. The COVID-19 pandemic affected influenza surveillance in all participating study sites, therefore the study period was truncated on February 29, 2020. Age-stratified (6 m-17y, 18-64y, ≥65y), confounder-adjusted, site-specific adjusted IVE estimates were calculated and pooled through meta -analysis. Parsimonious confounder-adjustment was performed, adjusting the estimates for age, sex and calendar time. TND studies included 3531 cases (351 vaccinated) and 5546 controls (1415 vaccinated) of all ages. IVE estimates were available for 8/11 brands marketed in Europe in 2019. Most children and adults < 64y were captured in primary care setting and the most frequently observed vaccine brand was Vaxigrip Tetra. The estimate against any influenza for Vaxigrip Tetra in primary care setting was 61% (95%CI 38–77) in children and 32% (95%CI −13–59) in adults up to 64y. Most adults ≥ 65y were captured in hospital setting and the most frequently observed brand was Fluad, with an estimate of 52% (95%CI 27–68). The population-based cohort covered 511, 854 person-years and two vaccine brands. In children aged 2-6y, the IVE against any influenza was 68% (95%CI 58–75) for Fluenz Tetra and 71% (56–80) for Vaxigrip Tetra. In adults ≥ 65y, IVE against any influenza was 29% (20–36) for Vaxigrip Tetra. DRIVE is a growing platform. Public health institutes with surveillance data and hospitals in countries with high influenza vaccine coverage are encouraged to join DRIVE.